The Use of Flowchart in Improving Students’ Ability in Writing Paragraph - Abdullah Syukur; Edi Wahyono (Ethical Lingua: Journal of Language Teaching and Literature, 2021)
This research aimed at finding out the use of flowchart in improving the ability of the fifth semester students of Informatics Engineering Study Program of Cokroaminoto Palopo University to write paragraph and to find out the interest of the students to write paragraph by using flowchart. This research was pre-experimental. Independent variable of the research is using flowchart in writing a paragraph and dependent variable is the ability of students to write a paragraph. The population of the research was the fifth semester students of Informatics Engineering Study Program of Universitas Cokroaminoto Palopo. The sample was one class of the fifth semester students of Informatics Engineering Study Program of Universitas Cokroaminoto Palopo. The result shows that flowchart is effective to use in improving students’ ability in writing because there was a significant difference between the progresses in writing of the students who were studying through flowchart and those are not. By flowchart strategy, the students can express their ideas easily without stopping and rushing. It gave them writing power and easy to understand.